ОЦІНКА РОБОТИ ЕЛЕКТРОСТАНЦІЙ ПРИ НАДАННІ ДОПОМІЖНИХ ПОСЛУГ З ПЕРВИННОГО ТА ВТОРИННОГО РЕГУЛЮВАННЯ ЧАСТОТИ В ОЕС УКРАЇНИ - Кириленко, О.В.; Блінов , І.В.; Парус , Є.В. (Інститут електродинаміки НАН України, Київ, 2013)
The models and methods of evaluation the power plant costs in services provision of primary and secondary frequency control are described. The costs evaluation is based on the calculation of opportunity costs resulting from the necessity of holding active power reserves to the needs of frequency control. This models and methods are an integral part of the methodology of price formation in the ancillary services market. They are oriented on solving the problem of stimulating power generators to provide services of the primary and secondary frequency control in the Ukrainian power system. These opportunity costs are the costs of power that could be used by the owner of the generating unit of power plant for selling electricity on the wholesale market. The model considers situations when electricity production becomes unprofitable due to reduction of market prices. The methods allow determining the power plant costs depending on the situation which is prevailing on the electricity market of Ukraine. The methods can be used in pool model and in balancing electricity market model. References 10, figures 4.